مقارنة بين طرق تكبير الصور الرقمية - الحان انور يونس; ايمان هشام عبد الرحمن (University of Mosul-college of Basic Education, 2013)
The research interested in digital image zooming from (128x128) to (256x256) using three of the zooming methods namley; Bilinear Interpolation, Nearest Neighbour Interpolation, and Linear Interpolation methods, then image difference measures (PSNR, MSE) computed for each output image from the three methods.The results show that Nearest Neighbour Interpolation is the best method. The research programmed using matlab language Ver. 7.